2023
DOI: 10.3390/nano13040724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structure and Composition of Adsorbents on Competitive Adsorption of Gaseous Emissions: Experiment and Modeling

Abstract: Dangerous gases arising from combustion processes must be removed from the air simply and cheaply, e.g., by adsorption. This work is focused on competitive adsorption experiments and force field-based molecular modeling of the interactions at the molecular level. Emission gas, containing CO, NO, SO2, and CO2, was adsorbed on activated carbon, clay mineral, silicon dioxide, cellulose, or polypropylene at two different temperatures. At 20 °C, activated carbon had the highest NO and SO2 adsorption capacity (120.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…In the case of SO 2 adsorption, the dominant interaction is the formation of hydrogen bonds with functional groups present on the surface. The work of Verner et al [ 51 ] demonstrated a high affinity of SO 2 for the surface of various adsorbents (activated carbon, bentonite, and silica gel) which was interpreted by both the porosity and the chemical nature of the surface of these materials.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of SO 2 adsorption, the dominant interaction is the formation of hydrogen bonds with functional groups present on the surface. The work of Verner et al [ 51 ] demonstrated a high affinity of SO 2 for the surface of various adsorbents (activated carbon, bentonite, and silica gel) which was interpreted by both the porosity and the chemical nature of the surface of these materials.…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption-based processes are generally determined by the adsorbent's surface chemical composition and textural properties [44,45]. Due to their very favorable properties, carbonaceous materials are especially attractive for the adsorption of both organic and inorganic solutes from the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%